2001
DOI: 10.1002/ijpg.227
|View full text |Cite
|
Sign up to set email alerts
|

Retire to where? A discrete choice model of residential location

Abstract: Many studies of migration attempt to identify attributes of places that in¯uence residential location decisions. Most such studies relate an area's migration rates to its own attributes, or the¯ow of migrants between two areas to the attributes of both places. We focus on retirement migration within the US, and extend the literature by using a discrete choice framework in which a person's location decision depends on the attributes of all potential locations. Using a multinomial logit speci®cation and 1990 Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 34 publications
2
30
0
1
Order By: Relevance
“…These procedures reduce our individual-level sample to 28,922 persons. Following established practice (Duncombe et al 2001; Mare and Bruch 2003; McFadden 1978), we impose a further limit on the sample size (the number of individuals and the number of street segments on which they resided) in order to stay within our computational capacity for discrete choice models (the computational load is the number of individuals multiplied by the number of street segments, more than 4 million observations.) After some experimentation, we found that the optimum size was a 10 % random sample (2,894 individuals), including as possible options all 1,442 residential street segments in which a sampled person of any group lived.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These procedures reduce our individual-level sample to 28,922 persons. Following established practice (Duncombe et al 2001; Mare and Bruch 2003; McFadden 1978), we impose a further limit on the sample size (the number of individuals and the number of street segments on which they resided) in order to stay within our computational capacity for discrete choice models (the computational load is the number of individuals multiplied by the number of street segments, more than 4 million observations.) After some experimentation, we found that the optimum size was a 10 % random sample (2,894 individuals), including as possible options all 1,442 residential street segments in which a sampled person of any group lived.…”
Section: Methodsmentioning
confidence: 99%
“…The multivariate analysis is based on discrete choice models for residential location (Duncombe et al 2001; Bruch and Mare 2006, 2012; McFadden 1973, 1978; Quillian 2015). The discrete choice model is suited for conditions where people choose from among a set of options.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, they find that elderly migrants are more likely to move towards states where the costs of public government policies are mainly borne by individuals who are still active in the labour market. The composition of local revenues and spending is found to play an important role also at the county level (Duncombe et al, 2001).…”
Section: Determinants Of Old Age Migrationmentioning
confidence: 95%
“…That is, already established retirement communities which facilitate information and can provide resources (Bradley & Longino, 2009;Conway & Houtenville, 2003;Conway & Rork, 2004;Cuba, 1991;Duncombe, Robbins, & Wolf, 2001;Jensen & Deller, 2007;Massey et al 1993;Ritchey 1976;Wiseman & Roseman, 1979). In other words, a link exists between select origins and destinations both spatially and temporally.…”
Section: Objectives and Hypothesismentioning
confidence: 95%